Patient engagement in the inpatient setting: a systematic review. (28th October 2013) - Prey, Jennifer E; Woollen, Janet; Wilcox, Lauren; Sackeim, Alexander D; Hripcsak, George; Bakken, Suzanne; Restaino, Susan; Feiner, Steven; Vawdrey, David K
Abstract: Objective To systematically review existing literature regarding patient engagement technologies used in the inpatient setting. Methods PubMed, Association for Computing Machinery (ACM) Digital Library, Institute of Electrical and Electronics Engineers (IEEE) Xplore, and Cochrane databases were searched for studies that discussed patient engagement ('self-efficacy', 'patient empowerment', 'patient activation', or 'patient engagement'), (2) involved health information technology ('technology', 'games', 'electronic health record', 'electronic medical record', or 'personal health record'), and (3) took place in the inpatient setting ('inpatient' or 'hospital'). Only English language studies were reviewed. Results 17 articles were identified describing the topic of inpatient patient engagement. A few articles identified design requirements for inpatient engagement technology. The remainder described interventions, which we grouped into five categories: entertainment, generic health information delivery, patient-specific information delivery, advanced communication tools, and personalized decision support. Conclusions Examination of the current literature shows there are considerable gaps in knowledge regarding patient engagement in the hospital setting and inconsistent use of terminology regarding patient engagement overall. Research on inpatient engagement technologies has been limited, especially concerning the impact on health outcomes and cost-effectiveness.